Women in Western political thought - Okin, Susan Moller (Princeton University Press, 2013)
In this pathbreaking study of the works of Plato, Aristotle, Rousseau, and Mill, Susan Moller Okin turns to the tradition of political philosophy that pervades Western culture and its institutions to understand why the gap between formal and real gender equality persists. Our philosophical heritage, Okin argues, largely rests on the assumption of the natural inequality of the sexes. Women cannot be included as equals within political theory unless its deep-rooted assumptions about the traditional family, its sex roles, and its relation to the wider world of political society are challenged.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; inégalités; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes; états-unis

Justice, genre et famille - Okin, Susan Moller (Champs (Flammarion (Firme)), 2008)
Considérant que "le mariage et la famille, tels qu'ils sont pratiqués dans notre société, sont des institutions injustes", Susan Moller Okin refuse toutefois de se contenter de montrer en quoi ils favorisent l'inégalité entre les hommes et les femmes. Car il faut aussi et surtout, à ses yeux, défendre la nécessité d'étendre la réflexion sur la justice à la sphère familiale. Sa question primordiale est de savoir dans quelle mesure il est possible de faire co-exister la justice et le genre.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; care; cours; discipline; europe; famille; france; mariage; phi2030; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis